Crystal structure of 3,4-bis[2-(hydroxymethyl)-pyrrolidin-1-yl] cyclobut-3-ene-1,2-dione hydrate, C14H22N2O5 - Wang Yiyu; Dang Xiaolin; Du Mo; Zhao Meimei; Tang Wenqiang (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C14H22N2O5, orthorhombic, P212121 (no. 19), a = 8.0704(12) Å, b = 9.0136(13) Å, c = 20.596(3) Å, V = 1498.2(4) Å3, Z = 4, Rgt(F) = 0.0429, wRref(F2) = 0.1112, T = 296 K.